Exploratory and Confirmatory Factor Analysis of the 9-Item Utrecht Work Engagement Scale in a Multi-Occupational Female Sample: A Cross-Sectional Study - Willmer, Mikaela; Westerberg Jacobson, Josefin; Lindberg, Magnus (Frontiers in Psychology, 2019)
Objective: The aim of the present study was to use exploratory and confirmatory factor analysis to investigate the factorial structure of the 9-item Utrecht Work Engagement Scale (UWES-9) in a multi-occupational female sample. Method: A total of 702 women, originally recruited as a general population of 7-15-year-old girls in 1995 for a longitudinal study, completed the UWES-9. Exploratory factor analysis (EFA) was performed on half the sample, and confirmatory factor analysis (CFA) on the other half. Results: Exploratory factor analysis was conducted with one and three factors, and showed a clear one-factor structure. Confirmatory factor analysis with four different models (one-factor, bi-factor, three-factor, and higher-order) was then conducted. Goodness-of-fit statistics showed poor fit for all four models, with RMSEA never going lower than 0.166. Conclusion: Despite clear indication from exploratory factor analysis that a one-factor structure best fit the data, we were unable to find good model fit for a one-, two, or three-factor model using confirmatory factor analysis. As previous studies have also failed to reach conclusive results on the optimal factor structure for the UWES-9, further research is needed in order to disentangle the possible effects of gender, nationality and occupation on work engagement.